Should the global community welcome new oil discoveries? - Sylwia Bialek; Alfons J. Weichenrieder (Journal of Economics, 2022)
Oil discoveries affect global well-being through multiple channels. Focusing on the change in pollution, consumption and extraction cost paths, we build a multi-period model with (endogenous) oil phase out that allows us to assess whether oil windfalls may be welfare-enhancing. The assessment depends on the quality of the discovered resource, expressed as the extraction cost. Our findings suggest that even when faced with high environmental externalities and no internalization mechanism for them, new oil finds can be conducive to welfare. However, there may be no simple threshold below which the discovery is beneficial, but rather multiple intervals into which the extraction costs may fall.
Keywords: Q32; Q35; 330; Oil discovery; Windfall profit; Environmental cost; Herfindahl rule; Extraction cost; Endogenous phase-out